2014
DOI: 10.1186/1746-1596-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features of triple negative breast cancers: an experience from Pakistan

Abstract: BackgroundYoung age breast cancers are quite prevalent in our setup, a significant number of which exhibit triple negative phenotype. These cancers behave in an aggressive fashion and unresponsive to targeted adjuvant therapy. We aimed to evaluate clinical and histopathologic features of triple negative cancers in our population.MethodsWe retrospectively evaluated 1104 cases of primary breast cancers. Immunohistochemical studies for ER, PR and Her2neu followed by Her2neu gene amplification by FISH testing were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
(49 reference statements)
8
27
0
2
Order By: Relevance
“…This result is consistent with previous relevant reports [21]. There is no effective treatment for basal-like breast cancer (BLBC) because it lacks ER and PR and HER2 expression, thus precluding hormone treatment and trastuzumab treatment [22]. Effective molecular target of basal-like subtype breast cancer has been focused on.…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with previous relevant reports [21]. There is no effective treatment for basal-like breast cancer (BLBC) because it lacks ER and PR and HER2 expression, thus precluding hormone treatment and trastuzumab treatment [22]. Effective molecular target of basal-like subtype breast cancer has been focused on.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, from the most common diagnoses to least common found in TNBC were IC-NST, carcinoma with medullary features, ILC, metaplastic carcinoma of no special type, and mucinous carcinoma. This researches were in accordance with Hashmi et al (2014) and Wang et al (2016). 12,13 Various literatures were also found that TNBC generally had higher grade than non-TNBC.…”
Section: Resultssupporting
confidence: 84%
“…On comparision with NTNBC, they found high association of basal markers with the TNBC than NTNBC. Similar significant correlation between basal like tumor and negative hormone status was seen by Pillai SK et al 21 Choccalingam C et al 32 Hence, in our study there was a significant overlap between triple negative carcinomas and basal like carcinomas.…”
Section: Results and Observationssupporting
confidence: 74%